Foraging Behaviours and Diets of Wolves in the Queen Maud Gulf Bird Sanctuary, Nunavut, Canada - Wiebe, Nathan; Samelius, Gustaf; Alisauskas, Ray T.; Bantle, Jason L.; Bergman, Christoffer; de Carle, Robert; Hendrickson, Christopher J.; Lusignan, Alain; Phipps, Kimberley J.; Pitt, Jason (ARCTIC, 2009)
Predation patterns often reflect the abundance and distribution of prey although factors such as vulnerability and ease of prey capture also affect these patterns. Wolves (Canis lupus) rely primarily on ungulates throughout most of their range even though other foods can be locally and seasonally important. We combined direct observation of wolves and scat analyses to examine the foraging behaviours and diets of wolves in the Queen Maud Gulf Bird Sanctuary, Nunavut, Canada. We were especially interested in how wolves used birds (primarily geese, Chen spp.) that were nesting in large numbers and dense colonies in the sanctuary. Caribou (Rangifer tarandus), which occurred in 65% of all scats, and bird prey, found in 29%, were the most common foods in scats, and behavioural observations confirmed this pattern. This study showed that caribou were the main prey of wolves in the Queen Maud Gulf Bird Sanctuary but that wolves also preyed on vulnerable and seasonally abundant foods, such as migratory birds, especially in late summer when ducks and geese were flightless during their annual remigial molt. Souvent, les modèles de prédation sont le reflet de l’abondance et de la répartition des proies, bien que des facteurs tels que la vulnérabilité et la facilité de capture des proies exercent également une influence sur ces modèles. Les loups (Canis lupus) font principalement la prédation d’ongulés quasiment à la grandeur de leur parcours, quoique d’autres sources de nourriture puissent également être importantes selon les endroits et les saisons. Nous avons recouru à l’observation directe des loups et à l’examen des excréments pour déterminer les comportements de recherche de nourriture et les régimes alimentaires des loups du Refuge d’oiseaux du golfe Reine-Maud, au Nunavut, Canada. Nous nous sommes particulièrement intéressés à la manière dont les loups se servaient des oiseaux (surtout les oies, Chen spp.) qui nidifiaient en grands nombres et faisaient partie de colonies denses au refuge. Le caribou (Rangifer ...